Bifidobacterium inhibits the progression of colorectal tumorigenesis in mice through fatty acid isomerization and gut microbiota modulation - Yang Chen; Huiting Fang; Haiqin Chen; Xiaoming Liu; Jianxin Zhao; Catherine Stanton; R. Paul Ross; Wei Chen; Bo Yang (Gut Microbes)
Colorectal cancer (CRC) represents the third most common cancer worldwide. Consequently, there is an urgent need to identify novel preventive and therapeutic strategies for CRC. This study aimed to screen for beneficial bacteria that have a preventive effect on CRC and to elucidate the potential mechanisms. Initially, we compared gut bacteria and bacterial metabolites of healthy volunteers and CRC patients, which demonstrated that intestinal conjugated linoleic acid (CLA), butyric acid, and Bifidobacterium in CRC patients were significantly lower than those in healthy volunteers, and these indicators were significantly negatively correlated with CRC. Next, spontaneous CRC mouse model were conducted to explore the effect of supplemental CLA-producing Bifidobacterium on CRC. Supplementation of mice with CLA-producing Bifidobacterium breve CCFM683 and B. pseudocatenulatum MY40C significantly prevented CRC. Moreover, molecular approaches demonstrated that CLA and the CLA-producing gene, bbi, were the key metabolites and genes for CCFM683 to prevent CRC. Inhibitor intervention results showed that PPAR-γ was the key receptor for preventing CRC. CCFM683 inhibited the NF-κB signaling pathway, up-regulated MUC2, Claudin-1, and ZO-1, and promoted tumor cell apoptosis via the CLA-PPAR-γ axis. Additionally, fecal microbiota transplantation (FMT) and metagenomic analysis showed that CCFM683 up-regulated Odoribacter splanchnicus through CLA production, which then prevented CRC by producing butyric acid, up-regulating TJ proteins, regulating cytokines, and regulating gut microbiota. These results will contribute to the clinical trials of Bifidobacterium and the theoretical research and development of CRC dietary products.